2010
DOI: 10.1111/j.1468-1331.2010.03001.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized convexity subarachnoid haemorrhage – a sign of early cerebral venous sinus thrombosis

Abstract: Localized SAH (whether focal, unilateral or bilateral), especially when confined to the parasagittal or dorsolateral convexity of the brain and without involvement of the basal cisterns, may provide an early pointer towards an underlying CVST. The presence of predisposing factors for CVST accords a further diagnostic hint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Another possible mechanism is venous hypertension and subsequent rupture of dilated, valveless, thin-walled, bridging subarachnoid cortical veins devoid of smooth muscle fibers. 6,7,12,16,17) This mechanism is consistent with previous reports, 17,20) and our study showed that cortical SAH usually occurs in the region adjacent to thrombosed veins or sinuses.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Another possible mechanism is venous hypertension and subsequent rupture of dilated, valveless, thin-walled, bridging subarachnoid cortical veins devoid of smooth muscle fibers. 6,7,12,16,17) This mechanism is consistent with previous reports, 17,20) and our study showed that cortical SAH usually occurs in the region adjacent to thrombosed veins or sinuses.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, intraparenchymal findings of venous hemorrhagic infarction were observed in only one of ten patients with cortical SAH due to CVT. 17) However, selection of SAH patients is likely to exclude patients with venous hemorrhagic infarction associated with secondary SAH, who would be classified as having intracerebral hemorrhage, not SAH. Another possible mechanism is venous hypertension and subsequent rupture of dilated, valveless, thin-walled, bridging subarachnoid cortical veins devoid of smooth muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations